Strategi Digitalisasi Arsip Pernikahan sebagai Upaya Preservasi Arsip Statis di KUA Kecamatan Medan Labuhan - Junaidi Junaidi; Nurul Amelia Hrp; Hany Handayani; Raihan Asri; Zahratul Hayat; Nurul Khodifa Yasmin; Arfah Sofwani (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
. The preservation of static archives in the Office of Religious Affairs (Kantor Urusan Agama/KUA) plays a crucial role in safeguarding the legal and administrative evidence of marriage for the community. However, many marriage records created between 1978 and 2002 at the Office of Religious Affairs of Medan Labuhan Subdistrict have experienced physical deterioration due to age, storage limitations, and environmental factors. Based on archival observations, out of 51 archival bundles (2,550 records), 76.4% were categorized as damaged, while only 23.5% remained in good condition. This condition highlights the urgency of implementing a systematic digitalization strategy as an effort to preserve static archives and ensure long-term access. This study aims to analyze the implementation of marriage archive digitalization as a preservation strategy and to examine its effectiveness in maintaining the authenticity, integrity, and accessibility of archival records. The research employs a qualitative descriptive approach through observation, documentation analysis, and field-based data interpretation. The findings indicate that digitalization contributes significantly to minimizing physical handling, preventing further deterioration, improving retrieval efficiency, and strengthening archival security. Nevertheless, several challenges were identified, including limited technological infrastructure, lack of standardized procedures, and human resource constraints. The study concludes that digitalization is not merely a technological transition but a strategic preservation effort that requires institutional commitment, proper archival management standards, and sustainable planning. By integrating digital preservation practices into archival governance, the Office of Religious Affairs can enhance the protection of marriage archives as static archives and ensure their continued legal and administrative value for future generations.